2019
DOI: 10.3390/cancers11111818
|View full text |Cite
|
Sign up to set email alerts
|

WWOX Possesses N-Terminal Cell Surface-Exposed Epitopes WWOX7-21 and WWOX7-11 for Signaling Cancer Growth Suppression and Prevention In Vivo

Abstract: Membrane hyaluronidase Hyal-2 supports cancer cell growth. Inhibition of Hyal-2 by specific antibody against Hyal-2 or pY216-Hyal-2 leads to cancer growth suppression and prevention in vivo. By immunoelectron microscopy, tumor suppressor WWOX is shown to be anchored, in part, in the cell membrane by Hyal-2. Alternatively, WWOX undergoes self-polymerization and localizes in the cell membrane. Proapoptotic pY33-WWOX binds Hyal-2, and TGF-β induces internalization of the pY33-WWOX/Hyal-2 complex to the nucleus fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(69 citation statements)
references
References 41 publications
(167 reference statements)
0
69
0
Order By: Relevance
“…Zfra binds to membrane Hyal-2 to activate spleen memory cytotoxic Z cells to kill cancer cells [ 2 , 6 , 10 , 11 , 12 , 13 ]. Additionally, when Hyal-2/pY33-WWOX/SMAD4 complex is overexpressed, hyaluronan binds to Hyal-2 and activates the signaling of Hyal-2/pY33-WWOX/SMAD4 to cause apoptosis in vivo [ 2 , 6 , 10 , 11 , 12 , 13 ]. To establish the role of Hyal-2 and WWOX in cancer suppression, nude mice received tail vein injections with sterile Milli-Q water or Zfra4-10 peptide (1 mM in 100 μL sterile Milli-Q water) in every two other days for three times.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Zfra binds to membrane Hyal-2 to activate spleen memory cytotoxic Z cells to kill cancer cells [ 2 , 6 , 10 , 11 , 12 , 13 ]. Additionally, when Hyal-2/pY33-WWOX/SMAD4 complex is overexpressed, hyaluronan binds to Hyal-2 and activates the signaling of Hyal-2/pY33-WWOX/SMAD4 to cause apoptosis in vivo [ 2 , 6 , 10 , 11 , 12 , 13 ]. To establish the role of Hyal-2 and WWOX in cancer suppression, nude mice received tail vein injections with sterile Milli-Q water or Zfra4-10 peptide (1 mM in 100 μL sterile Milli-Q water) in every two other days for three times.…”
Section: Resultsmentioning
confidence: 99%
“…In our recent study, we have demonstrated that ceritinib, an anaplastic lymphoma kinase (ALK)-positive inhibitor for lung cancer treatment [ 23 , 24 ], is able induce breast cancer stem cell sphere explosion and death [ 10 ]. Whether activated Z cells attacked and killed cancer cells and cancer stem cell spheres in vitro was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations